Modi the challenge of 2024 the battle for India - Merchant, Minhaz (Noida Amaryllis, 2023)
The Opposition$1 (Bs 26-party Indian National Developmental Inclusive Alliance (INDIA) aims to pose a serious challenge to the BJP-led National Democratic Alliance (NDA) in the 2024 Lok Sabha election. Despite the coalition leaders$1 (Bideological differences and regional rivalries, their overwhelming intent is to prevent Narendra Modi from becoming the first Indian since Jawaharlal Nehru to win three successive five-year prime ministerial terms. The 2024 Lok Sabha election could prove historic. If Narendra Modi wins a third successive five-year prime ministerial term, he will be the first Indian leader to do so since Jawaharlal Nehru. In this sweeping account of events leading up to the 2024 General Election, Minhaz Merchant analyses how Modi has shaped Indian politics, economics and culture during his decade as prime minister. The book examines whether the Opposition$1 (Bs strategy to present a united front can derail the BJP$1 (Bs juggernaut. For example, can Congress leader Rahul Gandhi, West Bengal Chief Minister Mamata Banerjee and regional satraps in Opposition-ruled states put aside their differences? Minhaz Merchant has met and interviewed Modi several times since 2012.s
Keywords: Narendra Modi; Politics and Government